2013
DOI: 10.5430/bmr.v1n2p125
|View full text |Cite
|
Sign up to set email alerts
|

Action Research on Blended Learning Transformative Potential in Higher Education- Learners’ Perspectives

Abstract: This article reports on action research on Blended learning approach conducted in 2011. The goal of the research was to investigate students' perspectives towards blended approach (hybrid) in teaching Business Communication as the learner progresses through their Executive program at Executive Development Centre, Universiti Utara Malaysia. Results indicated that students were in favor of BL. Students felt they learned as much or more than they did in traditional method of teaching and learning, were more motiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…It caters to the applied knowledge of personal reflection, collaborative thinking, and continual process improvements. In addition, it is also aligned with our considerations of purpose, appropriateness, multimodality, and sustainability across lessons, programs, and the institution (Dzakiria et al, 2013). Action research is directed toward the continuous improvement of teaching practices that undergo cycles of action and reflection (Cohen et al, 2000; Warden et al, 2013).…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…It caters to the applied knowledge of personal reflection, collaborative thinking, and continual process improvements. In addition, it is also aligned with our considerations of purpose, appropriateness, multimodality, and sustainability across lessons, programs, and the institution (Dzakiria et al, 2013). Action research is directed toward the continuous improvement of teaching practices that undergo cycles of action and reflection (Cohen et al, 2000; Warden et al, 2013).…”
Section: Methodsmentioning
confidence: 97%
“…In Hao (2016), blended learning is understood as the “inverted classroom” or the “reversed instructional model” that combines face-to-face live instructions with online learning activities and has been regarded as a viable method for delivering higher education programs. One of the salient features of blended learning practices adopted in the classroom is the convergence of synchronous technologies with a face-to-face learning environment, all happening in real time (Dzakiria et al, 2013; Warden et al, 2013). According to Johnson et al (2016), blended learning helps enhance students’ classroom experience and extends their learning through the innovative use of technology-enhanced web tools.…”
Section: The Web 20 Hypementioning
confidence: 99%
“…(Setyaningrum, 2018). Blended learning is also able to increase students' knowledge to a higher level of thinking, by developing student reasoning and motivation, which is based on studentcentered approaches (Dzakiria, Wahab, & Abdul Rahman, 2013;Russell, 2014;Powell, et al, 2015;Murtikusuma, et al, 2019). This model is able to take advantage of a variety of learning to be able to meet students' needs personally based on their learning style, level of knowledge, passion, abilities, and skills (Baro, 2011).…”
Section: Figure 1 Interaction Test Between Learning Classes With Initmentioning
confidence: 99%
“…An introduction to BL and its evaluation have been presented comprehensively by Boyer (2017). Similarly, University Malaysia Utara reported the use of BL method using action research in business communication in 2011, resulting in positive outcomes (Dzakiria, Don, Wahab, & Rahman, 2012). Freeman, et al (2014) reported the results of meta-analysis from 225 studies comparing active and traditional learning methods in science, technology, engineering, and mathematics (STEM) courses.…”
Section: Introductionmentioning
confidence: 99%